Magazine publishing - Johnson, Sammye; Prijatel, Patricia (Illinois: NTC College Publishing, 2000)
Contents: part one: the enduring medium. chapter 1. the magazine as a storehouse: the scape of a medium. chapter 2. the magazine as a marketplace: the role of advertising. 3. the magazine as a historical document. 4. the magazine as a social barometer. part two: the magazine's blueprint: 5. magazine concepts. 6. magazine business plans. 7. magazine structures. par three the magazine's content: 8. magazine editorial. 9. magazine designs. 10. magazine production. 11. magazine legalities. 12. magazines for the twenty - first century..
Es acompañado con un manual para el instructor, ver el inv. 2346
Keywords: Publicidad - Estados Unidos